Uji Aktivitas Antibakteri Ekstrak Metanol Daun Ramania (Bouea. macrophylla Griffith) Terhadap Bakteri Escherichia coli - hairunnisa nisa; Fitriyanti Fitriyanti; Putri Kartika Sari (Universitas Borneo Lestari, 2023)
Ramania (B. macrophylla Griffith) can beused as an antibacterial in the gastrointestinal tractOne of the bacteria in the digestive tract is Escherichia coli. The purpose of this study was to determine the group of compounds contained in ramania leaf methanol extract (B. macrophylla Griffith) and the activity of ramania leaf methanol extract (B. macrophylla Griffith) in inhibiting the growth of E. coli bacteria. Using the maceration method with methanol solvent and extract amendment of 8.6019%. Ramania leaf methanol extract (B. macrophylla Griffith) contains secondary metabolite compounds namely alkaloids, flavonoids, saponins, tannins, and steroids. Antibacterial activity test was carried out by the welling method with a concentration of methanol extract of ramania leaves (B. macrophylla Griffith) which is 1,024 mg / ml; 2,048 mg/ml; 4,096 mg/ml; 8.192 mg/ml; 16,384 mg/ml; 32,760 mg/ml; positive control of ciprofloxacin 5μg/disk, and negative control of Na-CMC 0.5%. The results of the antibacterial activity test of ramania leaf methanol extract (B. macrophylla Griffith) showed that the concentration of 2.048 mg / ml included the inhibition zone of the weak category, namely 3.33 mm;, while the concentration of 32,760 mg / ml included the moderate inhibition zone, namely mm; 8.48 mm and the positive control of ciprofloxacin 5μg / disk was included in the category of very strong inhibition zone, namely 22.8 mm. Based on the spss results using the Man-Whitney test the positive control and control had no difference due to the sig value (<0.05). It can be concluded that ramania leaf methanol extract (B. macrophylla Griffith) has antibacterial activity against E. coli bacteria and has secondary metabolite compounds found in ramania leaves (B. macrophylla Griffith) are Alkaloids, Flavonoids, Tannins, Saponins and Steroids.